Barriers Perceived by Medical and Faculty Members for the Implementation of Virtual Classroom During the Covid-19 Pandemic in Nepal - Pramila Poudel; Ramesh Ghimire; Asmita Subedi (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2022)
Background: A virtual classroom allows learner and educator to connect online in real time through digital learning environment. The present study sought to identify the barriers perceived by medical and nursing faculty members for the implementation of virtual classroom which was executed in Nepal to stay up with the scholarly schedule after nationwide lockdown due to COVID -19.Methods: This descriptive cross-sectional study was conducted from December 2020 to April 2021 among 77 faculty members of National Medical College, Teaching Hospital, Parsa, Nepal using convenience sampling technique. Data were collected using a semi structured, self-administered questionnaire. The obtained data were analyzed through SPSS version 23, using descriptive statistics.Results: The study findings revealed that the mean age of 77 faculty members was 35.35±6.46 years, with a minimum of 25 and maximum of 72years. The majority of the participants (59.7%) were male faculty members. As to academic qualification, 87% had completed postgraduate level. Regarding their current academic position, 74% were lecturer. Similarly, 38.9% of the faculty members were from clinical department. The results revealed that the faculty members perceived “Difficult to teach the practical content which requires demonstration” as a major barrier under technological barrier domain with a mean value of 4.30±1.027. “Difficulties in working from home” was as a major barrier under institutional barrier with a mean value of 3.44±1.164. Similarly, “Lack of control over students’ cheating” was found to be a major barrier under interpersonal barrier domain with a mean value of 4.14±0.884.Conclusion: This study identified the barriers felt by medical and nursing educators while implementing virtual classes as an alternative to physical classroom. It is important to plan effective strategies to overcome the potential challenges in implementing quality virtual classes